2009
DOI: 10.21273/hortsci.44.2.401
|View full text |Cite
|
Sign up to set email alerts
|

Substrate Depth Influences Sedum Plant Community on a Green Roof

Abstract: Because the waterproofing membrane beneath green roofs is estimated to last at least 45 years, long-term plant performance beyond initial establishment is critical. Plants that survive initially on a green roof may not exist in the long term because of variability in climate and other factors. This study evaluated the effect of green roof substrate depth on substrate moisture, plant stress as measured by chlorophyll fluorescence, and plant community development and survival of 12 Sedum Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
1
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(38 citation statements)
references
References 34 publications
2
30
1
4
Order By: Relevance
“…Overall, succulents were found to perform best in 7-10 cm of growth media across northern regions according to specific green roof design parameters (Table 2), but were found to tolerate 5-cm-deep substrates as well. Findings in the South Central Great Lakes ecoregion revealed that succulents performed marginally on very shallow (2.5-5 cm depths) unirrigated green roof research plots, better in 5-7.5 cm deep substrates (Durhman et al, 2007;Getter and Rowe, 2009) and better yet in 7-10 cm deep substrates (Getter and Rowe, 2008a,b,c). In general, Sedum were found to be very reliable genus as they were found to have great endurance for drought tolerance.…”
Section: Findings On Succulent Vegetationmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, succulents were found to perform best in 7-10 cm of growth media across northern regions according to specific green roof design parameters (Table 2), but were found to tolerate 5-cm-deep substrates as well. Findings in the South Central Great Lakes ecoregion revealed that succulents performed marginally on very shallow (2.5-5 cm depths) unirrigated green roof research plots, better in 5-7.5 cm deep substrates (Durhman et al, 2007;Getter and Rowe, 2009) and better yet in 7-10 cm deep substrates (Getter and Rowe, 2008a,b,c). In general, Sedum were found to be very reliable genus as they were found to have great endurance for drought tolerance.…”
Section: Findings On Succulent Vegetationmentioning
confidence: 99%
“…A similar investigation in Michigan also found sensitivity of Sedum ssp. roots to low temperatures in shallow substrates (2.5-7 cm), however plants were not growing on rooftops but on elevated platforms (Durhman et al, 2004(Durhman et al, , 2007Getter and Rowe, 2009). Some Sedum species also had poor performance in hot humid regions, where they did not tolerate the hot and humid evenings during summer (Livingston et al, 2004).…”
Section: Findings On Succulent Vegetationmentioning
confidence: 99%
“…Factors determining plant survival include media composition and depth 11,12 , incoming solar radiation 13 , climate and most importantly soil moisture [14][15][16] . Insufficient moisture can be remedied by altering media composition and depth or with irrigation if available.…”
Section: Definition Of Green Roofsmentioning
confidence: 99%
“…There have been a number of studies on the development of green roof vegetation over reasonably long periods, many of them concluding that plant diversity is dependent on the properties of the substrate (Bates et al, 2013;Thuring & Dunnett, 2014). Other studies have identified a relationship between the evolution of vegetation and the availability of water, as well as the depth of the substrate (Dunnett & Nolan, 2004;Getter & Rowe, 2009;Rowe et al, 2012).…”
Section: Introductionmentioning
confidence: 99%